PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN DAN SISTEM REMUNERASI TERHADAP KINERJA MANAJERIAL MELALUI KOMITMEN TUJUAN ANGGARAN DAN MOTIVASI SEBAGAI VARIABEL INTERVENING (STUDI PADA SATUAN KERJA PERANGKAT DAERAH KABUPATEN KARANGANYAR) - Widianto, Tri; Haryanto, Aris Tri (Jurnal Bulletin, 2018)
Effect of Participation in Budget Preparation and Remuneration System on Managerial Performance through Budget Purpose Commitment and Motivation as Intervening Variables (Study in the Karanganyar District Regional Work Unit). This study aims to generate a budget and its influence on intervening variables. (Study in the Karanganyar District Regional work device). The population in this study were 706 officials in the Regional Work Unit (SKPD) of Karanganyar Regency. The number of respondents studied was 255 respondents with 14 SKPD as research objects consisting of 1 Secretary, 1 Inspectorate, 1 Office, 4 Agencies, and 7 Departments. Testing hypotheses in this study using path analysis. Significant budgeting participation in commitment to budget objectives. Budgeting participation has a significant effect on motivation. The remuneration system has a significant effect on motivation. Budgetary participation is significant to managerial performance. Significant budget goal commitment to managerial performance. Motivation has a significant effect on managerial performance. The remuneration system is not significant to managerial performance. Strengthen the parts needed to achieve effective and effective goals. Effect of remuneration system on performance through direct relationships. Remuneration system variables through factors that influence managerial functions in the Regional Work Unit of Karanganyar Regency